Intermediate Algebra: Connecting Concepts through Application

Published by Brooks Cole
ISBN 10: 0-53449-636-9
ISBN 13: 978-0-53449-636-4

Chapter 3 - Exponents, Polynomials and Functions - 3.3 Composing Functions - 3.3 Exercises: 31

Answer

$\text{a) } f(g(5))=-55 \\\\\text{b) } g(f(5))=-129$

Work Step by Step

$\bf{\text{Solution Outline:}}$ With \begin{array}{l}\require{cancel} f(x)= 3x+8 \\g(x)= -6x+9 ,\end{array} to find $ f(g(5)) ,$ find first $ g(5) .$ Then substitute the result in $f.$ To find $ g(f(5)) ,$ find first $ f(5) .$ Then substitute the result in $g.$ $\bf{\text{Solution Details:}}$ a) Replacing $x$ with $ 5 $ in $g$ results to \begin{array}{l}\require{cancel} g(x)=-6x+9 \\\\ g(5)=-6(5)+9 \\\\ g(5)=-30+9 \\\\ g(5)=-21 .\end{array} Replacing $x$ with the result above in $f$ results to \begin{array}{l}\require{cancel} f(x)=3x+8 \\\\ f(-21)=3(-21)+8 \\\\ f(-21)=-63+8 \\\\ f(-21)=-55 .\end{array} Hence, $ f(g(5))=-55 .$ b) Replacing $x$ with $ 5 $ in $f$ results to \begin{array}{l}\require{cancel} f(x)=3x+8 \\\\ f(5)=3(5)+8 \\\\ f(5)=15+8 \\\\ f(5)=23 .\end{array} Replacing $x$ with the result above in $g$ results to \begin{array}{l}\require{cancel} g(x)=-6x+9 \\\\ g(23)=-6(23)+9 \\\\ g(23)=-138+9 \\\\ g(23)=-129 .\end{array} Hence, $ g(f(5))=-129 .$ Therefore, \begin{array}{l}\require{cancel} \text{a) } f(g(5))=-55 \\\\\text{b) } g(f(5))=-129 .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.